2020
DOI: 10.1093/tas/txaa065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of space allowance and marketing strategy on growth performance of pigs raised to 165 kg

Abstract: A total of 976 pigs (PIC 327 × Camborough; PIC, Hendersonville, TN; initially 22.0 ± 1.53 kg body weight [BW]) were used in a 160-d growth study to evaluate the effects of increasing space allowance and varying marketing strategies on growth performance of pigs raised to market weights of ~165 kg. Pens of pigs were blocked by location within the barn and allotted to one of six treatments. Pen served as the experimental unit, and there were eight replicate pens per treatment. The first four treatments consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Pigs are subjected to several stressors in the production system including space restriction during the finishing phase. It has been documented by numerous studies that reduced floor space results in reduced growth performance ( Flohr et al, 2016 ; Johnston et al, 2017 ; Thomas et al, 2017 ; Carpenter et al, 2018 ; Lei et al, 2018 ; Wastell et al, 2018 ; Lerner et al, 2020 ) and increase the incidence of abnormal behavior, including aggression, and tail biting ( Anil et al, 2007 ; Montoro et al, 2021 ). However, the negative outcome of increased prevalence of skin lesions in low space allowance conditions has not been observed in all studies as shown by Johnston et al (2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Pigs are subjected to several stressors in the production system including space restriction during the finishing phase. It has been documented by numerous studies that reduced floor space results in reduced growth performance ( Flohr et al, 2016 ; Johnston et al, 2017 ; Thomas et al, 2017 ; Carpenter et al, 2018 ; Lei et al, 2018 ; Wastell et al, 2018 ; Lerner et al, 2020 ) and increase the incidence of abnormal behavior, including aggression, and tail biting ( Anil et al, 2007 ; Montoro et al, 2021 ). However, the negative outcome of increased prevalence of skin lesions in low space allowance conditions has not been observed in all studies as shown by Johnston et al (2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Pigs were provided one three-hole feeder in each pen, which confounds the results, because reduced performance could not be distinguished between competition at the feeder or floor space in the pen. Similar methods were used by Lerner et al (2020), which stocked pens with 14 -23 pigs per pen to achieve floor space allowances of 0.66 -1.17 m 2 per pig. While such methods may show decreasing performance it cannot be determined if it was due to the increased group size or floor space reduction.…”
Section: Complexity Of Floor Space Researchmentioning
confidence: 99%